Students' Mathematical Critical Thinking Ability with Project Based Learning (PjBL) Model Based on Local Culture - Susanto, Adhi; Zaenuri, Zaenuri; Rachmani Dewi, Nuriana (Journal of Primary Education, 2021)
Students' mathematical critical thinking skills are still low, this is because the learning is still monotonous. Therefore, it is necessary to implement student-based learning. The purpose of this study was to analyze the effectiveness of the local culture-based Project Based Learning model in improving the critical thinking skills of class VIII students. This study uses a quantitative research approach. This design involved two groups of subjects, the experimental class was given treatment in the form of giving a Project Based Learning model with ethnomathematical nuances based on local wisdom, while the control class was taught using conventional learning. The sample in this study were 30 students in the experimental class and 30 students in the control class. The results of this study are the effectiveness of learning using the PjBL model with an ethnomathematical nuance based on local culture in improving the critical thinking skills of eighth grade students. Value of Sig. in the experimental class, the results of 0.05 it means that H0 is rejected, in other words that the average posttest result of students' critical thinking skills classically has reached the minimum criteria completeness so that it can be said to be effective. The mean of the experimental class showed a result of 82.50, while the control class showed a result of 71.09. This shows that the average critical thinking ability of students in the experimental class is higher than the average critical thinking ability of students in the control class. The conclusion of this research is that the Project Based Learning (PjBL) Model Based on Local Culture is effective in improving the critical thinking skills of eighth grade students.